Eco-Mobile Learning for Enhancing Critical Thinking Skills Among University Students - Shendy Andrie Wijaya; Ery Tri Djatmika; Bambang Sugeng; Wening Patmi Rahayu (Universitas Negeri Malang, 2024)
Microeconomics learning aims to help students understand how economic concepts and theories can be used to analyze and solve economic problems in everyday life. The study aims to develop Eco-mobile learning applications as learning media intended to improve critical thinking skills in terms of the cognitive style of economic education students. This research followed the Lee and Owen’s development model with the stages of need assessment and analysis, design, development, implementation, and evaluation. The research subjects were 105 economic education students taking microeconomics courses. The results of the media expert's assessment of the Eco-mobile learning application media as a whole were 94%, material experts gave an assessment of 97.3%, and student and lecturer responses to the practicality of the Eco-mobile learning application were 86.4% and 95.2%. Meanwhile, the effectiveness of the media can be obtained from the results of the critical thinking post-test scores in the experimental and control classes. Based on the overall results, it can be concluded that the Eco-mobile learning application developed in this research is suitable for use and effective in improving critical thinking skills in terms of the cognitive style of economics education students. Keywords: Eco-mobile learning, Critical thinking skill, Cognitive style